Comparative analyses of muscle MRI and muscular function in anti-synthetase syndrome patients and matched controls: a cross-sectional study. Issue 1 (December 2017) - Andersson, Helena; Kirkhus, Eva; Garen, Torhild; Walle-Hansen, Ragnhild; Merckoll, Else; Molberg, Øyvind
Abstract Background Magnetic resonance imaging (MRI) of thigh muscles is increasingly used to assess disease activity and damage extent in chronic myositis, but the validity of the findings is not clear. Here, the primary aim was to compare thigh MRI findings in patients having chronic myositis associated with anti-synthetase syndrome (ASS) and in matched healthy controls. Methods Cross-sectional analyses of thigh muscle MRI, muscular function and creatinine kinase (CK) were performed in 68 ASS patients (median disease duration 71 months) and 67 controls matched for age and gender. MRI changes associated with disease activity (edema in muscles and fascia) and damage (fatty replacement and muscle volume reduction) were assessed semiquantitatively, giving a total MRI score of 0–78 (total edema 0–42 and total damage 0–36). Results ASS patients had higher total MRI score than the matched controls (14.1 versus 3.0;p < 0.001) and less muscle strength (p < 0.001). Muscle edema was more frequent in ASS patients than controls (38% versus 12%), as was fatty replacement (42% versus 4%). In ASS patients, we found that the total edema score correlated with CK, but 23% of the patients with normal CK had score > 18. Muscle compartment analyses in ASS patients showed that muscle edema was most pronounced anteriorly, while fatty replacement dominated posteriorly. Conclusions This study showed, for the first time, the magnitude of difference in muscle MRI findings between chronic myositis cases and matched controls. In ASS patients, muscle MRI appeared to provide useful complementary information to muscle strength and CK levels in the assessment of myositis.